The Effect of Sol-Gel Temperature and Solvent Polyethylene Glycol (PEG) in ZnO-TiO2 Photocatalyst Activity as Degrader of Textile Dyeing Liquid Waste - Tanti Haryati; Novita Andarini; Siti Mardhiyah (UNIVERSITAS SEBELAS MARET (UNS), 2016)
The use of TiO2 powder as photocatalyst still provides some disadvantages such as the difficulties in regenerate ion, the low adsorption and turbulence . These problems can be overcomed by providing the photocatalyst as a composite of ZnO-TiO2. This research aims to investigate the effect of composition of solvent and temperatureof synthesis on the quality and photocatalytic activity of ZnO-TiO2 which was prepared by sol-gel method. The photocatalytic activity was determined by applying the composite in degradation of Procion Red MX-8B under irradition of UV light for 24 hours. The procion red concentration after degradation was determined by UV-Vis spectrophotometer. Meanwhile the effect of synt hesis temperature on crystal structure of composite was studied by XRD. The results show that the composite which was prepared by PEG 1500 at 1:4 of moles ratio and at 70 °C of synthesis temperature has highest degradation percentage, i.e. 55.375 % and photocataltic activity of 3.561 x 10-7mg/cm2s.